Formula allocation: The regional allocation of budgetary funds for measures of active labour market policy in Germany - Uwe Blien (European Regional Science Association (ERSA), 2003)
In Germany, the funds for active labour market policy – e.g. training measures and job creation schemes – are paid from a common budget, the so-called integration title. For the allocation of budgetary funds (amounting to exteuro 13 billion every year) to the regions of the Federal Republic of Germany, a formula was developed which was to be based essentially on a labour market indicator. A proposal for the method of distribution (including the indicator) was developed at the IAB. The criteria for the development were: most accurate fit to the legal guidelines of the Social Code, transparency of the procedure, openness for necessary policy decisions, scientific correctness in implementation, efficiency of the whole process. Here the procedure used in constructing the indicator is explained and the distribution result is set out. This was finally passed by the Executive Board and the Board of Governors of the Federal Employment Service and contains the necessary business policy weightings. The history of the implementation of the instrument for the distribution of resources is also dealt with briefly.
Keywords: 330